Percolation description of charge transport in the random barrier model applied to amorphous oxide semiconductors. (16th October 2019) - Baranovskii, S. D.; Nenashev, A. V.; Oelerich, J. O.; Greiner, S. H. M.; Dvurechenskii, A. V.; Gebhard, F.
Abstract: Charge transport in amorphous oxide semiconductors is often described as the band transport affected by disorder in the form of random potential barriers (RB). Theoretical studies in the framework of this approach neglected so far the percolation nature of the phenomenon. In this article, a recipe for theoretical description of charge transport in the RB model is formulated using percolation arguments. Comparison with the results published so far evidences the superiority of the percolation approach.